(untitled) (Global Journal of Management and Business Research, 2011)
In this study the relationship between four Corporate Governance Mechanisms (board size, chief executive status, annual general meeting and audit committee) and two Firm Performance Measures (return on equity, ROE, and profit margin, PM), of Karachi Stock Exchange listed oil & gas firms is examinedfor the period 2004 -2010. The t-test and Multiple Regression analysis are applied to examine the significance & dependency of the above mentioned variables. By using the panel methodology and OLS as a method of estimation, the results provide an evidence of a significant effect and positive relationship between ROE and board size as well as annual general meeting. But ROE has negative relationship with audit committee and CEO status and both have significant effect on it. The results further expose a positive relationship between PM, board size and annual general meeting and they have no significant effect. The study, however, could not provide a significant effect between PM and audit committee. The CEO status and audit committee have a negative relationship with PM but CEO status has a significant effect. The implication of this is that the board size should be limited to a sizeable limit and that the post of the chief executive should be occupied by different persons.